Differential L-shell radiative recombination rate coefficients for bare uranium ions interacting with low-energy electrons - Banaś, Dariusz; Pajek, M.; Gumberidze, Alexandre; Surzhykov, Andrey; Stöhlker, Thomas (European physical journal special topics, 2013)
Results of the calculations of differential L−shell radiative recombination (RR) rate coefficients for bare uranium ions colliding with free electrons using the nonrelativistic dipole approximation and fully relativistic calculations are reported. The rate coefficients were obtained for very low, in the range of meV, relative electron-ion energies. We demonstrate that even for such low relative ion-electron energies the relativistic effects significantly modify the differential RR rate coefficients for the L−subshells and, as a result, the measurements of the relative electron energy dependence of the L-RR rates could be used for studying of the relativistic effects. These effects are strongest for the L3-subshell, which is discussed here in more details.
Gesehen am 28.10.2020